2010
DOI: 10.1016/j.jacc.2010.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Fat Is Independently Associated With Human Atrial Fibrillation

Abstract: Pericardial fat volume is highly associated with paroxysmal and persistent AF independent of traditional risk factors including left atrial enlargement. Whether pericardial fat plays a role in the pathogenesis of AF requires future investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
249
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(269 citation statements)
references
References 17 publications
10
249
1
9
Order By: Relevance
“…Al Chekakie et al (24) and Batal et al (25), referring to the association between pericardial fat volume and AF, suggested that the local effects of proinflammatory cytokines released from the pericardial adipose tissue may be a potential mechanism for the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Al Chekakie et al (24) and Batal et al (25), referring to the association between pericardial fat volume and AF, suggested that the local effects of proinflammatory cytokines released from the pericardial adipose tissue may be a potential mechanism for the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another study using a relatively large sample from the Framingham Heart Study (n=3,217) has also shown that pericardial fat volume was associated with AF even after adjustment for risk factors, including body mass index. 6 In addition, Wong et al recently reported that EAT volume assessed by magnetic resonance imaging (MRI) was significantly associated with AF chronicity and symptom burden, as well as the presence itself, and is predictive of long-term AF recurrence after ablation.…”
Section: Article P 2748mentioning
confidence: 99%
“…Ectopic fat deposits in muscle, liver, and the pancreas correlate with insulin resistance and CAD [4]. Epicardial adipose tissue (EAT) is ectopic visceral fat that surrounds the heart, and increased EAT volumes correlate with the prevalence of AF, as well as with the recurrence of AF after ablation therapy [6,7]. Increased fat thickness at the posterior left atrium (LA) may be particularly related to the AF burden, independent of age, BMI, and the LA area [8,9].…”
Section: Introductionmentioning
confidence: 99%